Development and Content Validation of a Psychomotor Assessment Instrument for Conventional Distributor-Type Diesel Fuel System Maintenance - Sugeng Riyadi; Tatang Permana; Muhammad Maris Al Gifari (Universitas Negeri Padang, 2026)
Psychomotor assessment in vocational high schools often remains subjective and insufficiently standardized, particularly in practical automotive learning related to conventional distributor-type diesel fuel systems. This study developed a performance assessment instrument to evaluate students’ technical competence in vocational automotive education more objectively. A Research and Development design adapted from Sugiyono’s model was applied up to the expert validation stage. The instrument comprised three integrated components: a Job Sheet, Work Sheet, and Assessment Sheet, structured using hierarchical indicators of psychomotor assessment from Imitation (P1) to Naturalization (P5). Five experts, consisting of three content experts and two assessment-instrument experts, evaluated the instrument using a four-point Likert scale. The validation data were analyzed using Aiken’s V to examine content, construct, language, and usability validity. The results showed that all components obtained Aiken’s V values above 0.80, indicating valid expert judgment across the assessed aspects. The developed instrument provides an initial valid basis for more structured, transparent, and consistent assessment of diesel fuel system maintenance skills in vocational practice.